2020
DOI: 10.1177/0284185119896520
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of whole-lesion apparent diffusion coefficient histogram analysis metrics for differentiating benign and malignant breast lesions: a systematic review and diagnostic meta-analysis

Abstract: Background Although whole-lesion apparent diffusion coefficient (ADC) histogram has been increasingly used for breast lesions, it has not been routinely used in clinical practice as an emergent promising imaging tool. Purpose To evaluate the performance of whole-lesion ADC histogram analysis metrics for differentiating benign and malignant breast lesions. Material and Methods A systematic PubMed/EMBASE/Cochrane electronic database search was performed for original diagnostic studies from 1 January 1970 to 2 Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A meta-analysis showed that apparent diffusion coefficient (ADC) histogram analysis has 85% sensitivity and 79% specificity in the accurate differentiation of malignant and benign breast lesions, as well as a good diagnostic performance. The same meta-analysis concluded that the 50 th percentile had the greatest accuracy among histogram parameters 20 .…”
Section: Discussionmentioning
confidence: 93%
“…A meta-analysis showed that apparent diffusion coefficient (ADC) histogram analysis has 85% sensitivity and 79% specificity in the accurate differentiation of malignant and benign breast lesions, as well as a good diagnostic performance. The same meta-analysis concluded that the 50 th percentile had the greatest accuracy among histogram parameters 20 .…”
Section: Discussionmentioning
confidence: 93%
“…Although the usefulness of the ADC value as an imaging biomarker has been reported in various malignancies, ADC values are affected by several image-dependent factors, including differences in gradient, coil, pulse-sequence system, and acquisition parameters [17]. The usefulness of skewness and kurtosis, which are less affected by these settings in ADC-related factors, obtained using histogram analysis is being investigated [18]. In this study, the diagnostic model using ADC map-based texture features showed high diagnostic performance comparable to intracross validation, unlike the mean ADC value alone, despite the differences between the two patient cohorts and MRI machines.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of diffusion-weighted imaging in breast MRI has been an area of intensive investigations lately (75,76) as well as the role of background parenchymal enhancement as an imaging biomarker for breast cancer risk (77) (Figure 2). DCE-MRI has, in many settings, an important role in preoperative staging (78).…”
Section: Magnetic Resonance Imaging Of the Breastmentioning
confidence: 99%